1990
DOI: 10.1161/01.hyp.16.5.555
|View full text |Cite
|
Sign up to set email alerts
|

Intrarenal de novo production of angiotensin I in subjects with renal artery stenosis.

Abstract: To estimate the renal extraction and de novo production of angiotensin I and to assess the contribution of blood-borne renin to renal angiotensin I production, the aortic and renal venous plasma levels of renin and intact [ I] angiotensin I and endogenous angiotensin I during continuous systemic intravenous infusion of monoiodinated [I25 I]angiotensin I were measured in subjects with unilateral renal artery stenosis (n=8) who were treated with captopril (50 mg b.i.d.). Results demonstrated that 80% of angioten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

1992
1992
2007
2007

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 23 publications
1
9
0
Order By: Relevance
“…Thus, because the plasma levels of endogenous Ang I in the aorta have been reported to be only 20% lower than in the right atrium and the peripheral veins, 21 our results indicate that 30-40% of the conversion of blood-borne Ang I occurs outside the lungs. In a similar way (by using Equation 15), it can be calculated that only about 15% of Ang I delivered to the central circulation is degraded into peptides other than Ang II during a single passage of blood from the right atrium to the aorta, whereas 35-50% of Ang I delivered to the systemic circulation is degraded during a single passage of blood from the aorta to the right atrium, indicating that at least 70-80% of the degradation of blood-borne Ang I occurs outside the lungs. We were unable to detect any Ang I-to-II conversion in the kidneys both in URAS and in EHT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, because the plasma levels of endogenous Ang I in the aorta have been reported to be only 20% lower than in the right atrium and the peripheral veins, 21 our results indicate that 30-40% of the conversion of blood-borne Ang I occurs outside the lungs. In a similar way (by using Equation 15), it can be calculated that only about 15% of Ang I delivered to the central circulation is degraded into peptides other than Ang II during a single passage of blood from the right atrium to the aorta, whereas 35-50% of Ang I delivered to the systemic circulation is degraded during a single passage of blood from the aorta to the right atrium, indicating that at least 70-80% of the degradation of blood-borne Ang I occurs outside the lungs. We were unable to detect any Ang I-to-II conversion in the kidneys both in URAS and in EHT.…”
Section: Discussionmentioning
confidence: 99%
“…14 ' 15 In addition, some de novo production of Ang I occurs in circulating plasma by PRA, during the passage of blood from the arterial to the venous side of the vascular bed. Regional venous Ang I derived from arterial delivery could be calculated from the results obtained during infusion of 125 I-Ang I alone as follows:…”
Section: Calculationsmentioning
confidence: 99%
“…The lowest values were observed for the 24 hours of the 30th treatment day in the group treated by osmopumps. Because plasma Ang II is not the best index of local production of Ang II and most Ang I and Ang II are produced outside of the plasma, 24 the rise in PRC, which reflects the interruption of the intrarenal feedback loop between Ang II and renin release, may represent a more sensitive index of the degree of RAS blockade. 25 Indeed, PRC was much higher in CI rats, at both day 1 and day 30, especially 24 hours after gavage, which demonstrates a more complete and continuous blockade of the RAS in rats treated by osmopumps.…”
Section: Discussionmentioning
confidence: 99%
“…In 249 subjects, of which 68% were hypertensive, both systolic and diastolic blood pressure negatively correlated with the renal plasma flow response to Ang II (Perlstein et al, 2004). Admiraal et al (1990) showed the intrarenal RAS activation in patients with essential hypertension by tracer studies. Intravenous infusion of 125 I-Ang I allowed estimation of de novo production of Ang I in the kidney, which corresponded to 80% of the renal venous plasma concentration of Ang I. Estimation of Ang I-to-II conversion in the kidney also demonstrated local synthesis of Ang II (Admiraal et al, 1993).…”
Section: B Clinical Studiesmentioning
confidence: 96%